Evaluating and adapting new technologies in a high-risk agricultural system - Niger - Shapiro, Barry I.; Sanders, J.H.; Reddy, K.C.; Baker, T.G. (Elsevier, 1993)
This study modeled the introduction of new early cultivars of millet and cowpea, higher cowpea densities, and various fertilization strategies. Model results were then compared with farmer behaviour before and after the availability of these new technologies. The model correctly identified the two new technologies being adopted by farmers. Then further runs of the adaptive model identified several research-extension strategies to increase the adoption of fertilization. Some recommendations to researchers and extension agents were made. The intraseasonal adaptive decision-making process of farmers was modeled with a one-year, discrete stochastic sequential programming whole-farm model.